Lower genitourinary tract trauma. (January 2016) - Bayne, David; Zaid, Uwais; Alwaal, Amjad; Harris, Catherine; McAninch, Jack; Breyer, Benjamin
Lower genitourinary tract trauma comprises a substantial portion of the trauma burden in the USA. Some key trends and findings are described. Mortality is relatively high in patients with bladder trauma due to associated injuries. Urethral injuries should be suspected in patients presenting with the triad of blood at the urethral meatus, suprapubic fullness indicative of a full bladder, and urinary retention. Urethral injury is common in penetrating penile trauma, and stab wounds to the penis are more likely to involve the urethra than gunshot wounds. Penile fracture is largely a clinical diagnosis and suspicion of fracture requires urgent surgical exploration. Zipper injuries are the most common cause of presentation to the emergency department for penile trauma in adults. Toilet seat injuries are the leading cause of penile pediatric trauma presenting to the emergency department. In the setting of testicular trauma, rates of testicular salvage are excellent when exploration is prompt. Trauma in the form of animal or human bites requires treatment with broad-spectrum antibiotics in addition to repair of the injury. Military trauma has seen an increase in explosive injuries to the lower urinary tracts due to evolution of warfare tactics. Increasing awareness of presentation and context of lower genitourinary tract trauma can reduce delay of diagnosis and morbidity associated with such injuries.